Perfil de resistência a antimicrobianos em Staphylococcus spp isolados de mastite em bovinos leiteiros no Agreste paraibano - Silva, Camila Pereira da (2021)
Staphylococcus spp. stand out as the most frequent etiological agents of bovine mastitis,with high levels of resistance to antimicrobials, especially to beta-lactams, thus limiting the choice of antibiotics for treatment. Thereby, this study aimed to determine the resistance profile of Staphylococcus spp to different classes of antimicrobials and to phenotypically evaluate theoccurrence of Staphylococcus spp. resistant to methicillin and resistance caused by efflux pump in isolates of bovine mastitis in the state of Paraíba, Brazil. 326 milk samples from cows withclinical and subclinical mastitis were collected and submitted to microbiological examination for isolation and identification of Staphylococcus spp. To study sensitivity and resistance of Staphylococcus spp to antimicrobials, the disk diffusion technique was used against the main antibiotics used to treat this disease in the region. To assess resistance to methicillin, the disk diffusion test on MH agar with cefoxitin (30 mcg) and oxacillin (1mcg) was used, and for phenotypic detection of the efflux system, the disk diffusion test on MH agar with norfloxacin (10 mcg) was used. Of the 326 milk samples analyzed, 60 strains of Staphylococcus spp. wereisolated, being 83.3% (50/60) S. aureus, 8.33% (5/60) S. chromogenes, 5% (3/60) S. epidermidis and 3.33% (2/60) S. sciuri . Antimicrobial susceptibility tests showed little variation in the isolates' resistance profiles. Isolates resistant to penicillin sensitive to the otherdrugs tested constituted the predominant resistance pattern. All isolates studied were sensitive to oxacillin and cefoxitin, except for 5 strains of S. aureus, 1 strain of S. chromogenes and 1 strain of S. epidermidis, which showed resistance to oxacillin and 2 strains of S. epidermidis, which showed resistance cefoxitin, being considered phenotypically resistant to methicillin. The phenotypic detection of efflux system was not observed in this study, since all Staphylococcus sp. evaluated were sensitive to norfloxacin. The phenomenon of multiple antimicrobial resistance was not observed in this study, however, the phenotypic detection of MRSA is a concern and molecular methods should be used for better investigation.